Special composite adhesive film for main-grid-free photovoltaic module as well as preparation method and application of special composite adhesive film
By adopting a three-layer co-extruded composite adhesive film structure, the photocured isolation layer is used to limit the flow of the adhesive layer, the problem of adhesive film infiltration in the main gate photovoltaic module is solved, and the bonding strength and long-term reliability of the module are improved. sex.
Patent Information
- Application Number
- CN202411975426.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing packaging film for photovoltaic modules without main gates can prevent the film from penetrated into the welding tape and the secondary gate through the pre-crosslinking support layer, but this method results in a low bonding strength between the adhesive film and the battery cell. Impacts the long-term reliability of components.
A three-layer co-extruded composite adhesive film structure is adopted, including a adhesive film layer, an isolation layer and an adhesive layer. The isolation layer is composed of a photosensitive resin prepolymer and a photoinitiator. The adhesive layer contains an amphiphilic polymer and passes through the isolation layer. The photocuring of the photocuring reduces its fluidity, thereby limiting the flow of the bonding layer and preventing infiltration.
While avoiding the adhesive film infiltration between the welding tape and the secondary gate, the bonding strength between the composite adhesive film and the battery cell is improved, the production process is simplified, and the long-term reliability and photoelectric conversion efficiency of photovoltaic modules are improved.
Smart Images

Figure CN119391312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic encapsulation adhesive films, and in particular to a composite adhesive film special for busbar-free photovoltaic modules, and a preparation method and application thereof. Background Art
[0002] With the continuous development of photovoltaic power generation technology, cost reduction and efficiency improvement have gradually become the main theme of the industry. In order to improve the charge collection capacity of crystalline silicon photovoltaic cells, metal silver paste will be used to make grid lines. According to estimates, metal silver ranks second in the cost of photovoltaic modules. Therefore, reducing silver consumption will greatly reduce the cost of modules. Busbar-free technology is currently one of the most effective means to reduce silver consumption, especially for HJT cells that use a large amount of silver paste, which can effectively reduce the amount of silver paste by 30%~45%. In addition, busbar-free technology uses finer sub-grids to minimize the shading area on the surface of crystalline silicon cells and improve battery conversion efficiency.
[0003] For busbar-free modules, since the busbar is omitted, the welding strip needs to form an ohmic contact with the secondary grid directly. The traditional string welding technology cannot achieve this requirement, and the new welding technology will increase the cost and weaken the profit gain brought by reducing silver consumption. The encapsulation film is a protective layer directly covering the battery cell and the welding strip. It can be used to fit the welding strip and the secondary grid tightly to achieve good ohmic contact. At present, the commonly used photovoltaic films on the market cannot meet the packaging requirements of busbar-free battery modules. During the lamination process, the molten flow of the film will penetrate into the space between the welding strip and the secondary grid in the battery cell to form an insulating layer, resulting in a virtual connection phenomenon in the module.
[0004] Invention patent CN117153916A discloses an isolation film for photovoltaic modules, a composite film for photovoltaic modules, and a photovoltaic module, which are matched with a film layer, a support layer, and an adhesive layer. The support layer is pre-crosslinked so that the flow rate of the adhesive layer during the lamination process is limited by the support layer. At the same time, the thickness of the adhesive layer is designed to be less than the height of the welding strip, so that the welding strip is not easily embedded in the adhesive layer during the lamination process, thereby effectively avoiding the virtual connection caused by the film penetrating between the welding strip and the auxiliary grid during the lamination process. However, in the above patent, the support layer after pre-crosslinking treatment cannot be co-extruded with the film layer and the adhesive layer, and needs to be laid layer by layer during preparation, resulting in a long production process and complicated process; and in this patent, the bonding strength between the adhesive layer and the battery cell is low, which will lead to poor long-term reliability of the photovoltaic module.
[0005] Invention patent CN117025108A discloses a packaging film for HJT battery components without main grid, its preparation method and photovoltaic components. The packaging film is made by two-layer co-extrusion. In order to avoid the film from penetrating into the welding strip and the auxiliary grid to form a virtual connection during the lamination process, one of the layers is irradiated and pre-crosslinked, which is called the support layer. When the photovoltaic module is made, the support layer is laminated with the battery cell. Although this method can solve the virtual connection problem, the pre-crosslinking treatment will seriously reduce the bonding strength between the film and the battery cell, especially for HJT batteries with a TCO layer on the surface, thereby reducing the long-term reliability of the component. Summary of the invention
[0006] In order to solve the above technical problem, that is, the existing packaging film for busbar-free photovoltaic modules is pre-crosslinked with the support layer to which the battery cell is attached to prevent the film from penetrating into the welding strip and the auxiliary grid to form a virtual connection, and this method has the problem of low bonding strength between the film and the battery cell. The present invention provides a composite film for busbar-free photovoltaic modules, a preparation method and application thereof. The present invention can prevent the composite film from penetrating into the welding strip and the auxiliary grid during lamination, while making the composite film have a higher bonding strength with the battery cell, and the composite film can be prepared by a three-layer co-extrusion method, which is relatively simple and efficient when used.
[0007] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a composite adhesive film specially used for busbar-free photovoltaic modules, which comprises, from top to bottom, an adhesive film layer, an isolation layer, and an adhesive layer bonded to the welding strip and the battery cell in the photovoltaic module; the periphery of the adhesive film layer is bonded to the periphery of the adhesive layer to wrap the isolation layer; the raw materials of the isolation layer include photosensitive resin prepolymer and photoinitiator; the raw materials of the adhesive layer include matrix resin and amphiphilic polymer; the melt flow rate of the isolation layer after photocuring is less than the melt flow rate of the adhesive layer.
[0008] The isolation layer in the present invention uses photosensitive resin prepolymer and photoinitiator as raw materials. Before photocuring, the isolation layer raw materials have good fluidity, so they can be co-extruded with the film layer and the bonding layer through three-layer co-extrusion; after the three-layer co-extrusion is completed, photocuring is performed, which can make the isolation layer have lower fluidity (i.e., less than the melt flow rate of the bonding layer). When the composite adhesive film thus formed is used in a photovoltaic module, during the lamination process of the photovoltaic module, the isolation layer that is in contact with the bonding layer and has lower fluidity can limit the flow of the bonding layer, thereby preventing the bonding layer from penetrating between the welding strip and the secondary grid in the battery cell and causing a virtual connection phenomenon of the module. Through the above-mentioned method, while avoiding the composite adhesive film from penetrating between the welding strip and the secondary grid, the composite adhesive film can be prepared by a three-layer co-extrusion method. When in use, there is no need to lay the bonding layer, the isolation layer and the film layer layer layer by layer, which can make the production process of the photovoltaic module shorter and the production process simpler.
[0009] On this basis, the present invention adopts the design of "the periphery of the film layer is fitted with the periphery of the adhesive layer to wrap the isolation layer inside", which can prevent the isolation layer with higher fluidity from being lost from the composite film before light curing, thereby ensuring that the isolation layer can better play its role of "limiting the flow of the adhesive layer" during lamination.
[0010] Moreover, the problem of the adhesive film penetrating between the welding strip and the auxiliary grid during the lamination process is solved by setting an isolation layer (rather than by increasing the cross-linking degree of the adhesive layer), thereby avoiding the negative impact of the adhesive strength between the composite adhesive film and the battery cell due to the increased cross-linking degree of the adhesive layer. In addition, the present invention adds an amphiphilic polymer to the adhesive layer, and the incompatibility of its hydrophilic segment and lipophilic segment will cause microphase separation, so that the amphiphilic polymer exhibits self-assembly characteristics in the bulk and surface interface structure, so that good contact can be formed at the interface between the adhesive layer and the welding strip, and the adhesive layer and the battery cell, thereby improving the adhesion between the adhesive layer and the battery cell and the welding strip, ensuring that the welding strip is firmly fixed on the battery cell, so that the welding strip and the auxiliary grid are firmly combined together to form an effective ohmic contact, and the photovoltaic module has good long-term reliability and still has a high bonding strength after aging.
[0011] Preferably, the weight average molecular weight of the amphiphilic polymer is 1-3 kDa.
[0012] By increasing the molecular weight of the amphiphilic polymer, the bonding strength between the composite adhesive film and the solder ribbon and the battery cell can be improved; however, when the molecular weight of the amphiphilic polymer is too high, the adhesive layer is not easy to spread on the surface of the battery cell, which will have an adverse effect on the bonding strength between the composite adhesive film and the solder ribbon and the battery cell.
[0013] Preferably, the amphiphilic polymer is a graft copolymer or block copolymer consisting of a hydrophilic segment and a hydrophobic segment; the hydrophilic segment includes one or more of polyethylene glycol, polyvinyl ether, polyvinyl alcohol, polyethyleneimine, polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid and polystyrene sulfonate; the hydrophobic segment includes one or more of polypropylene oxide, polystyrene, polysiloxane, polyolefin, polymethyl methacrylate, polymethyl acrylate and polybutyl acrylate.
[0014] Preferably, the amphiphilic polymer is a graft copolymer consisting of a polyethylene glycol main chain and a polypropylene oxide side chain.
[0015] Preferably, the thickness of the isolation layer and the bonding layer are 50-100 μm and 50-150 μm respectively; the thickness of the bonding layer is smaller than the thickness of the welding strip.
[0016] The isolation layer has a high hardness after photocuring and contains a large number of unsaturated functional groups. By controlling the thickness of the isolation layer to 50~100μm, it can avoid damage to the battery cells during the lamination process and prevent hidden cracks in the photovoltaic modules, which would reduce the photoelectric conversion efficiency.
[0017] The thickness of the above-mentioned welding strip refers to: when the photovoltaic module is laid flat, the vertical distance between the highest point of the welding strip located above the battery cell and the battery cell.
[0018] Preferably, the melt flow rate of the isolation layer after photocuring at 120°C and a load of 2.16kg is 1.0~5.0g / 10min; the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 3.0~10.0g / 10min; at 120°C and a load of 2.16kg, the melt flow rate of the isolation layer after photocuring is 1.0~9.0g / 10min less than the melt flow rate of the bonding layer.
[0019] Preferably, the isolation layer comprises the following raw materials in parts by weight: 100 parts of photosensitive resin prepolymer, 1-1.5 parts of photoinitiator, and 0-2 parts of isolation layer auxiliary agent; the isolation layer auxiliary agent comprises a reactive diluent.
[0020] Preferably, the photosensitive resin prepolymer includes one or more of acrylated epoxy resin, unsaturated polyester, polyurethane, polythiol photocurable resin and polyene photocurable resin.
[0021] Preferably, the photoinitiator includes one or more of a benzoin photoinitiator, an acetophenone photoinitiator and a triarylthiobell salt photoinitiator.
[0022] Preferably, the reactive diluent includes a free radical reactive diluent and / or a cationic reactive diluent.
[0023] Preferably, the bonding layer comprises the following raw materials in parts by weight: 100 parts of base resin, 1-2 parts of amphiphilic polymer, and 0.1-3 parts of bonding layer additives; the bonding layer additives include one or more of cross-linking agents, auxiliary cross-linking agents, silane coupling agents, tackifying resins, antioxidants, light stabilizers, and processing aids.
[0024] Preferably, the base resin includes one or more of ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), thermoplastic polyolefin (TPO), polyvinyl butyral (PVB) and silicone.
[0025] Preferably, the adhesive film layer is a polyolefin elastomer (POE) adhesive film, an ethylene-vinyl acetate copolymer (EVA) adhesive film or a polyvinyl butyral (PVB) adhesive film.
[0026] The film layer can be made of conventional encapsulation film, such as POE film, EVA film, or PVB film.
[0027] In a second aspect, the present invention provides a method for preparing the composite adhesive film, comprising the following steps: preparing an adhesive film layer mixture and an adhesive layer mixture, and preparing an isolation layer mixture in the dark; performing three-layer co-extrusion molding in the dark, and then curing the isolation layer by ultraviolet irradiation to obtain the composite adhesive film.
[0028] In a third aspect, the present invention provides an application of the composite adhesive film in a busbar-less photovoltaic module, wherein the busbar-less photovoltaic module comprises a back panel, a first encapsulation film, a welding strip, a battery cell, a welding strip, a second encapsulation film and glass stacked in sequence from top to bottom; the first encapsulation film and / or the second encapsulation film is the composite adhesive film.
[0029] Preferably, in the busbar-less photovoltaic module, the isolation layer completely covers the solar cells.
[0030] By making the isolation layer completely cover the battery cell (i.e. making the isolation layer larger than the battery cell), it can be ensured that during lamination, the adhesive layer within the battery cell has lower fluidity due to the isolation layer, thereby effectively preventing the adhesive layer from penetrating between the solder ribbon and the auxiliary grid.
[0031] Compared with the prior art, the present invention has the following advantages: (1) The present invention utilizes an isolation layer with low fluidity to limit the flow of the adhesive layer during the lamination process. In this way, it is not necessary to increase the degree of cross-linking of the adhesive layer in contact with the battery cell, thereby preventing the composite adhesive film from penetrating between the solder ribbon and the auxiliary grid during lamination to cause a virtual connection, thereby avoiding an adverse effect on the bonding strength between the composite adhesive film and the battery cell.
[0032] (2) The composite adhesive film of the present invention adopts a three-layer composite structure of an adhesive film layer, an isolation layer and an adhesive layer, and the isolation layer adopts a photosensitive resin prepolymer and a photoinitiator as raw materials. This can prevent the composite adhesive film from penetrating into the space between the welding strip and the auxiliary grid during lamination to cause a virtual connection, while enabling the composite adhesive film to be prepared by a three-layer co-extrusion molding method. When in use, it does not need to be laid layer by layer, thereby shortening the production process of photovoltaic modules and simplifying the production process.
[0033] (3) The present invention can improve the bonding strength between the composite adhesive film and the battery cell by adding an amphiphilic polymer to the bonding layer, so that the photovoltaic module has better long-term reliability; on this basis, by controlling the molecular weight of the amphiphilic polymer, the bonding strength between the composite adhesive film and the battery cell can be further improved.
[0034] (4) The present invention can avoid the occurrence of hidden cracks in the photovoltaic module by controlling the thickness of the isolation layer, so that the photovoltaic module has a higher photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of a cross-sectional structure of a photovoltaic module in the present invention.
[0036] The reference numerals in the drawings are: composite adhesive film 1, adhesive film layer 11, isolation layer 12, adhesive layer 13, welding ribbon 2, battery cell 3. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] A composite adhesive film specially used for a busbar-free photovoltaic module comprises, from top to bottom, an adhesive film layer, an isolation layer and an adhesive layer bonded to a welding strip and a battery cell in the photovoltaic module; the periphery of the adhesive film layer is bonded to the periphery of the adhesive layer to wrap the isolation layer; the raw materials of the isolation layer include a photosensitive resin prepolymer and a photoinitiator; the raw materials of the adhesive layer include a matrix resin and an amphiphilic polymer; the melt flow rate of the isolation layer after light curing is less than the melt flow rate of the adhesive layer.
[0039] In some specific embodiments, the thickness of the isolation layer and the bonding layer are 50-100 μm and 50-150 μm, respectively; and the thickness of the bonding layer is smaller than the thickness of the welding strip.
[0040] In some specific embodiments, the melt flow rate of the isolation layer after photocuring at 120°C and a load of 2.16 kg is 1.0~5.0g / 10min; the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 3.0~10.0g / 10min; at 120°C and a load of 2.16kg, the melt flow rate of the isolation layer after photocuring is 1.0~9.0g / 10min less than the melt flow rate of the bonding layer.
[0041] In some specific embodiments, the adhesive film layer may be a conventional packaging adhesive film, including but not limited to a polyolefin elastomer (POE) adhesive film, an ethylene-vinyl acetate copolymer (EVA) adhesive film or a polyvinyl butyral (PVB) adhesive film.
[0042] In some specific embodiments, the isolation layer comprises the following raw materials in parts by weight: 100 parts of photosensitive resin prepolymer, 1-1.5 parts of photoinitiator, and 0-2 parts of isolation layer auxiliary agent. The isolation layer auxiliary agent includes but is not limited to active diluent; the active diluent includes but is not limited to free radical type active diluent and / or cationic type active diluent.
[0043] In some specific embodiments, the photosensitive resin prepolymer includes one or more of acrylated epoxy resin, unsaturated polyester, polyurethane, polythiol photocurable resin and polyene photocurable resin; the photoinitiator includes one or more of benzoin photoinitiator, acetophenone photoinitiator and triarylthiobell salt photoinitiator.
[0044] In some specific embodiments, the bonding layer comprises the following raw materials in parts by weight: 100 parts of base resin, 1-2 parts of amphiphilic polymer, and 0.1-3 parts of bonding layer additives. The bonding layer additives include, but are not limited to, one or more of a cross-linking agent, a co-cross-linking agent, a silane coupling agent, a tackifying resin, an antioxidant, a light stabilizer, and a processing aid.
[0045] In some specific embodiments, the base resin may be a conventional encapsulation film resin, including but not limited to one or more of ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), thermoplastic polyolefin (TPO), polyvinyl butyral (PVB) and silica gel.
[0046] In some specific embodiments, the amphiphilic polymer is a graft copolymer or block copolymer composed of a hydrophilic segment and a hydrophobic segment, and has a weight-average molecular weight of 1 to 3 kDa; the hydrophilic segment includes one or more of polyethylene glycol, polyvinyl ether, polyvinyl alcohol, polyethylene imine, polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid and polystyrene sulfonate; the hydrophobic segment includes one or more of polypropylene oxide, polystyrene, polysiloxane, polyolefin, polymethyl methacrylate, polymethyl acrylate and polybutyl acrylate.
[0047] A method for preparing the composite adhesive film comprises the following steps: preparing an adhesive film layer mixture and a bonding layer mixture, and preparing an isolation layer mixture in the dark; performing three-layer co-extrusion molding in the dark, and then curing the isolation layer by ultraviolet irradiation to obtain the composite adhesive film.
[0048] The composite adhesive film is used in a busbar-free photovoltaic module, which includes a backplane, a first packaging film, a welding strip, a battery cell, a welding strip, a second packaging film and glass stacked in sequence from top to bottom; the first packaging film and / or the second packaging film is the composite adhesive film.
[0049] In some specific embodiments, in the busbar-less photovoltaic module, the isolation layer completely covers the solar cell.
[0050] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0051] Example 1 The photovoltaic module structure of this embodiment is as follows Figure 1 As shown, the specific structure is as follows: It is composed of a back plate, a composite adhesive film 1, a soldering tape 2, a battery cell 3, a soldering tape 2, a composite adhesive film 1 and a glass stacked in sequence from top to bottom ( Figure 1 The backplane and glass are not shown); the composite adhesive film 1 is composed of an adhesive film layer 11, an isolation layer 12 and an adhesive layer 13 arranged in sequence from top to bottom; the periphery of the adhesive film layer 11 is bonded to the periphery of the adhesive layer 13, wrapping the isolation layer 12 on all sides; the welding tape 2 is cylindrical with a diameter of 0.2 mm; after lamination, the adhesive layer 13 is bonded to the welding tape 2 and the surface of the battery cell 3, the adhesive film layers 11 in the two composite adhesive films 1 are bonded to the backplane and the glass respectively, and the isolation layer 12 completely covers the battery cell 3.
[0052] The preparation method of the composite film used in this embodiment is as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0053] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0054] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0055] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.0g / 10min.
[0056] Example 2 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0057] The preparation method of the composite film used in this embodiment is as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0058] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1 part of 1-p-tolyl-2-diethylamino-1-propanone, and 0.1 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0059] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1.5 parts of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, molecular weight 3kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.2 parts of antioxidant 1076, 0.2 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0060] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 50μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 1.8g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.6g / 10min.
[0061] Example 3 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0062] The preparation method of the composite film used in this embodiment is as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0063] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.5 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 2 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0064] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 2 parts of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, molecular weight of 1kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0065] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 150μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 1.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.0g / 10min.
[0066] Example 4 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0067] The method for preparing the composite adhesive film used in this embodiment is different from that in Embodiment 1 only in that the thickness of the isolation layer is increased. The steps for preparing the composite adhesive film in this embodiment are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0068] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0069] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0070] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 80μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.0g / 10min.
[0071] Example 5 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0072] The method for preparing the composite adhesive film used in this embodiment is different from that in Embodiment 1 only in that the thickness of the isolation layer is increased. The steps for preparing the composite adhesive film in this embodiment are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0073] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0074] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0075] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 100μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.0g / 10min.
[0076] Example 6 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0077] The method for preparing the composite adhesive film used in this embodiment is different from that in Embodiment 1 only in that the type of photosensitive resin prepolymer in the isolation layer is changed. The steps for preparing the composite adhesive film in this embodiment are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0078] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of unsaturated polyester resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0079] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0080] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 4.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.0g / 10min.
[0081] Example 7 The photovoltaic module structure of this embodiment is the same as that of embodiment 1.
[0082] The method for preparing the composite adhesive film used in this embodiment is different from that in Embodiment 1 only in that the type of amphiphilic polymer in the adhesive layer is changed. The steps for preparing the composite adhesive film in this embodiment are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0083] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0084] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethyleneimine main chain and polysiloxane side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0085] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this embodiment, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120℃ and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120℃ and a load of 2.16kg is 5.3g / 10min.
[0086] Comparative Example 1 The photovoltaic module structure of this comparative example is different from that of Example 1 only in that the composite adhesive film 1 is composed of an adhesive film layer 11 and an adhesive layer 13 , and no isolation layer 12 is provided.
[0087] The method for preparing the composite adhesive film used in this comparative example is different from that in Example 1 only in that the isolation layer is eliminated. The steps for preparing the composite adhesive film in this comparative example are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0088] S2: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0089] S3: Molding and curing: The film layer mixture and the bonding layer mixture are added to the double-layer co-extrusion storage tank, respectively, and double-layer co-extrusion molding is performed, and then rolled up to obtain a composite film. In the composite film prepared in this comparative example, the thickness of the film layer is 300 μm and the thickness of the bonding layer is 100 μm; the melt flow rate of the bonding layer at 120° C. and a load of 2.16 kg is 5.0 g / 10 min.
[0090] Comparative Example 2 The photovoltaic module structure of this comparative example is the same as that of Example 1.
[0091] The method for preparing the composite adhesive film used in this comparative example is different from that in Example 1 only in that the thickness of the isolation layer is increased. The steps for preparing the composite adhesive film in this comparative example are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0092] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0093] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 1 part of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, weight average molecular weight of 2kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0094] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this comparative example, the thickness of the film layer is 300μm, the thickness of the isolation layer is 150μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120°C and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 5.0g / 10min.
[0095] Comparative Example 3 The photovoltaic module structure of this comparative example is the same as that of Example 1.
[0096] The method for preparing the composite adhesive film used in this comparative example is different from that in Example 1 only in that no amphiphilic polymer is added to the adhesive layer. The steps for preparing the composite adhesive film in this comparative example are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0097] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.2 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 0.7 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0098] S3: Preparation of bonding layer mixture: The following raw materials were weighed in parts by weight: 98 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the auxiliary agent was completely absorbed, a bonding layer mixture was obtained, which was placed in a storage bin for standby use.
[0099] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this comparative example, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 100μm; the melt flow rate of the isolation layer at 120°C and a load of 2.16kg after light curing is 2.0g / 10min, and the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 6.3g / 10min.
[0100] Comparative Example 4 The photovoltaic module structure of this comparative example is the same as that of Example 1.
[0101] The method for preparing the composite adhesive film used in this comparative example is different from that in Example 2 only in that the molecular weight of the amphiphilic polymer used in the adhesive layer is increased. The steps for preparing the composite adhesive film in this comparative example are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0102] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1 part of 1-p-tolyl-2-diethylamino-1-propanone, and 0.1 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0103] S3: Preparation of bonding layer mixture: The following raw materials were weighed in parts by weight: 98 parts of EVA resin, 1.5 parts of amphiphilic polymer (graft copolymer consisting of polyethylene glycol main chain and polypropylene oxide side chain, molecular weight 5kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.2 parts of antioxidant 1076, 0.2 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the auxiliary agent was completely absorbed, a bonding layer mixture was obtained, which was placed in a storage bin for standby use.
[0104] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this comparative example, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 50μm; the melt flow rate of the isolation layer at 120°C and a load of 2.16kg after light curing is 1.8g / 10min, and the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 4.9g / 10min.
[0105] Comparative Example 5 The photovoltaic module structure of this comparative example is the same as that of Example 1.
[0106] The method for preparing the composite adhesive film used in this comparative example is different from that in Example 3 only in that the molecular weight of the amphiphilic polymer used in the adhesive layer is reduced. The steps for preparing the composite adhesive film in this comparative example are as follows: S1: Preparation of film layer mixture: The following raw materials were weighed in parts by weight: 100 parts of EVA resin, 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, and 0.1 parts of light stabilizer UV770. The above raw materials were mixed at high speed, and after the additives were completely absorbed, a film layer mixture was obtained, which was placed in a storage bin for later use.
[0107] S2: Preparation of isolation layer mixture: The following raw materials were weighed in parts by weight: 100 parts of acrylated epoxy resin, 1.5 parts of 1-p-tolyl-2-diethylamino-1-propanone, and 2 parts of cationic reactive diluent (epoxy reactive diluent, purchased from Jiangmen Xinhui District Xinrixu Electronic Materials Co., Ltd.). The above raw materials were mixed at high speed under light-proof conditions. After the auxiliary agent was completely absorbed, the isolation layer mixture was obtained and placed in a light-proof storage bin for standby use.
[0108] S3: Preparation of bonding layer mixture: Weigh the following raw materials according to weight: 98 parts of EVA resin, 2 parts of amphiphilic polymer (graft copolymer composed of polyethylene glycol main chain and polypropylene oxide side chain, molecular weight 0.5kDa), 0.7 parts of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane triacrylate, 0.4 parts of γ-methacryloxypropyl trimethoxysilane, 0.1 parts of antioxidant 1076, 0.1 parts of light stabilizer UV770. Mix the above raw materials at high speed, and after the auxiliary agent is completely absorbed, obtain the bonding layer mixture, which is placed in the storage bin for standby use.
[0109] S4: Molding and curing: The film layer mixture, the isolation layer mixture and the bonding layer mixture are added to the three-layer co-extrusion storage tank respectively, and the three-layer co-extrusion molding is carried out under light-proof conditions, and then the ultraviolet lamp is used for uniform irradiation to completely cure the isolation layer, and then rolled up to obtain a composite film. In the composite film prepared in this comparative example, the thickness of the film layer is 300μm, the thickness of the isolation layer is 50μm, and the thickness of the bonding layer is 150μm; the melt flow rate of the isolation layer at 120°C and a load of 2.16kg after light curing is 1.0g / 10min, and the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 5.4g / 10min.
[0110] Test Case The composite adhesive films and photovoltaic modules in each embodiment and comparative example were tested for performance, and the results are shown in Table 1. The peel strength between the composite adhesive film and the HJT cell was tested according to the test method in GB / T 29848-2018, and the photoelectric conversion efficiency of the photovoltaic module was tested according to the test method in GB / T 34160-2017.
[0111] Table 1 Performance test results of composite film and photovoltaic modules
[0112] From Table 1 we can see that: (1) There is no shadow in the EL images of the photovoltaic modules of Examples 1 to 7, and the photoelectric conversion efficiency is higher than that of Comparative Example 1. This is because: on the basis of Comparative Example 1, Examples 1 to 7 add an isolation layer, which can limit the flow of the adhesive layer during the lamination process, thereby preventing the adhesive layer from penetrating between the soldering ribbon and the secondary grid in the cell to cause a virtual connection phenomenon of the module, thereby improving the photoelectric conversion efficiency of the photovoltaic module.
[0113] (2) Comparative Example 2 Based on Examples 1, 4 and 5, after increasing the thickness of the isolation layer, hidden cracks appeared in the photovoltaic module, and the photoelectric conversion efficiency of the photovoltaic module was significantly reduced. This is because: the isolation layer has a high hardness after photocuring and contains a large number of unsaturated functional groups. When its thickness is too large, it will damage the battery cell during lamination.
[0114] (3) In Example 1 and Example 7, amphiphilic polymers are added to the adhesive layer on the basis of Comparative Example 3, and the peel strength between the composite adhesive film and the HJT cell and the photoelectric conversion efficiency of the photovoltaic module are significantly improved. This is because: the incompatibility of the hydrophilic segment and the lipophilic segment in the amphiphilic polymer will cause microphase separation, so that the amphiphilic polymer exhibits self-assembly characteristics in the bulk and surface interface structure, so that good contact can be formed at the interface between the adhesive layer and the welding strip, and the adhesive layer and the cell, thereby improving the adhesion between the adhesive layer and the cell and the welding strip, ensuring that the welding strip is firmly fixed on the cell, so that the welding strip and the secondary grid are firmly combined together to form an effective ohmic contact, thereby improving the photoelectric conversion efficiency of the photovoltaic module.
[0115] (4) Comparative Example 4 increases the molecular weight of the amphiphilic polymer on the basis of Example 2, and the peel strength between the composite adhesive film and the HJT cell is reduced; Comparative Example 5 decreases the molecular weight of the amphiphilic polymer on the basis of Example 3, and the peel strength between the composite adhesive film and the HJT cell is also reduced. This is because: when the molecular weight of the amphiphilic polymer is too low, its viscosity enhancement effect is weak, and the bonding strength between the adhesive layer and the cell is low; when the molecular weight of the amphiphilic polymer is too high, the adhesive layer is not easy to spread on the surface of the cell, which will also have an adverse effect on the bonding strength between the adhesive layer and the cell.
[0116] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0117] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A composite adhesive film for busbar-free photovoltaic modules, characterized in that: From top to bottom, it includes a film layer, an isolation layer, and a bonding layer that is bonded to the welding strip and the battery cell in the photovoltaic module; the periphery of the film layer is bonded to the periphery of the bonding layer to wrap the isolation layer; the raw materials of the isolation layer include photosensitive resin prepolymer and photoinitiator; the raw materials of the bonding layer include base resin and amphiphilic polymer; the melt flow rate of the isolation layer after photocuring is lower than the melt flow rate of the bonding layer.
2. The composite adhesive film according to claim 1, characterized in that: The weight average molecular weight of the amphiphilic polymer is 1-3 kDa.
3. The composite adhesive film according to claim 1 or 2, characterized in that: The amphiphilic polymer is a graft copolymer or block copolymer composed of a hydrophilic segment and a hydrophobic segment; the hydrophilic segment includes one or more of polyethylene glycol, polyvinyl ether, polyvinyl alcohol, polyethylene imine, polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid and polystyrene sulfonate; the hydrophobic segment includes one or more of polypropylene oxide, polystyrene, polysiloxane, polyolefin, polymethyl methacrylate, polymethyl acrylate and polybutyl acrylate.
4. The composite adhesive film according to claim 3, characterized in that: The amphiphilic polymer is a graft copolymer consisting of a polyethylene glycol main chain and a polypropylene oxide side chain.
5. The composite adhesive film according to claim 1, characterized in that: The thickness of the isolation layer and the bonding layer are 50-100 μm and 50-150 μm respectively; the thickness of the bonding layer is smaller than the thickness of the welding strip.
6. The composite adhesive film according to claim 1, characterized in that: The melt flow rate of the isolation layer after photocuring at 120°C and a load of 2.16kg is 1.0~5.0g / 10min; the melt flow rate of the bonding layer at 120°C and a load of 2.16kg is 3.0~10.0g / 10min; at 120°C and a load of 2.16kg, the melt flow rate of the isolation layer after photocuring is 1.0~9.0g / 10min less than the melt flow rate of the bonding layer.
7. The composite adhesive film according to claim 1, characterized in that: The isolation layer comprises the following raw materials in parts by weight: 100 parts of photosensitive resin prepolymer, 0.1-1.5 parts of photoinitiator, and 0-2 parts of isolation layer auxiliary agent; the isolation layer auxiliary agent comprises an active diluent.
8. The composite adhesive film according to claim 1, characterized in that: The bonding layer comprises the following raw materials in parts by weight: 100 parts of base resin, 1-2 parts of amphiphilic polymer, and 0.1-3 parts of bonding layer additives; the bonding layer additives include one or more of crosslinking agents, auxiliary crosslinking agents, silane coupling agents, tackifying resins, antioxidants, light stabilizers, and processing aids.
9. A method for preparing the composite adhesive film according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: preparing a film layer mixture and a bonding layer mixture, and preparing an isolation layer mixture in a light-proof manner; performing three-layer co-extrusion molding in a light-proof manner, and then curing the isolation layer by ultraviolet irradiation to obtain the composite film.
10. The use of the composite adhesive film according to any one of claims 1 to 8 in a busbar-free photovoltaic module, characterized in that: The busbar-free photovoltaic module comprises a backplane, a first packaging film, a welding strip, a battery cell, a welding strip, a second packaging film and glass stacked in sequence from top to bottom; the first packaging film and / or the second packaging film is the composite film.
Citation Information
Patent Citations
Packaging adhesive film for main-grid-free HJT battery assembly, preparation method of packaging adhesive film and photovoltaic assembly
CN117025108A
Isolating film for photovoltaic module, composite film for photovoltaic module and photovoltaic module
CN117153916A
Photo-thermal dual-curing POE (Polyolefin Elastomer) multilayer packaging adhesive film
CN116004126A
Packaging adhesive film and photovoltaic module
CN116589940A
Composite adhesive film for packaging photovoltaic module as well as preparation method and application of composite adhesive film
CN117683476A